UI/UX Design of Mobile-Based Employee Performance Monitoring Using User-Centered Design Method PT Citra Digital Lintas - Wirlandika, Devri; Prayono, Tukino; Novalia, Elfina (Journal of Artificial Intelligence and Software Engineering, 2025)
Development of mobile-based employee performance monitoring application interface at PT Citra Digital Lintas using User-Centered Design (UCD) method and usability testing with Single Ease Question (SEQ). The results of the user needs analysis showed a priority on transparency and ease of access. In the evaluation phase, 7 key tasks were tested with 10 respondents. An average SEQ score of 7.0 indicated the interface was easy to use, with T8 (real-time monitoring) being the best task (average 7.0; 50% scored 7/very easy). A total of 80% of respondents scored 6/easy on tasks T3 (data input) and T7 (performance report), reflecting design consistency. However, T1 (multi-role login) had 20% scoring 4/difficult, the highest among the other tasks, although the average was still 5.1/quite easy. Overall, 7 out of 8 tasks fell into the moderately easy category (scores 5-6.9), while T8 was the only one to reach the easy category (scores ≥7). Improvement recommendations focused on T1 to reduce user barriers, while the design of T8 was retained as an intuitive reference. Implementation of the app improved monitoring efficiency (85% positive response) and supported performance transparency, with potential for increased accuracy (90% satisfaction) and employee engagement. These results confirm that the UCD approach and SEQ validation were effective in creating a solution that aligned with user and organisational needs.